2017
DOI: 10.3389/fimmu.2017.00720
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Endocrine System and the Immune System: A Review of the Inflammatory Role of Prolactin in Rheumatoid Arthritis and Psoriatic Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that affects females three times more frequently than males. A potential role for hormones, such as prolactin (PRL), may in part explain this phenomenon. The risk of developing RA is increased in women who are lactating after the first pregnancy, which might be related to breastfeeding and the release of PRL. Other studies found a protective effect of PRL on RA development. Some studies have reported that hyperprolactinemia is more common in RA and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 68 publications
0
47
0
Order By: Relevance
“…Studies on PRL levels in RA have provided inconsistent results with lower, higher, or equivocal values [139,147]. It has been shown that the risk and severity of RA are decreased in reproductive states characterized by hyperprolactinaemia (pregnancy and breastfeeding) [148].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Studies on PRL levels in RA have provided inconsistent results with lower, higher, or equivocal values [139,147]. It has been shown that the risk and severity of RA are decreased in reproductive states characterized by hyperprolactinaemia (pregnancy and breastfeeding) [148].…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Second, many clinical and preclinical studies show that endogenous release of PRL from both pituitary and extra-pituitary origins is induced by inflammation and tissue injury (Chernow et al, 1987; Noreng et al, 1987; BenJonathan et al, 1996; Yardeni et al, 2007; Scotland et al, 2011; Patil et al, 2013a). Third, PRL is an effective direct and/or indirect activator of immune cells, especially macrophages and T-cells (Matera et al, 2001; Savino et al, 2016; Tang et al, 2017). Moreover, many chronic autoimmune diseases affect females more frequently than males, and a potential role for PRL may in part explain this phenomenon for certain autoimmune diseases such as lupus (Tang et al, 2017; Rizzetto et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Third, PRL is an effective direct and/or indirect activator of immune cells, especially macrophages and T-cells (Matera et al, 2001; Savino et al, 2016; Tang et al, 2017). Moreover, many chronic autoimmune diseases affect females more frequently than males, and a potential role for PRL may in part explain this phenomenon for certain autoimmune diseases such as lupus (Tang et al, 2017; Rizzetto et al, 2018). Fourth, translational regulation of Prlr in sensory neurons has been suggested in our previous work (Patil et al, 2019b), and herein we show evidence in support of the translocation of Prlr mRNA to peripheral and central terminals of female or male sensory neurons where it could be translated in a female sex hormone specific fashion (Patil et al, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role played by prolactin in acute cerebral infarction, one could not separate between its immune-modulatory and thrombogenic effects. As a cytokine, PRL influences proliferation, regulation, and communication of inflammatory cells [4]. Furthermore, it leads to platelet activation and arterial thrombogenesis through direct enhancement of ADP and P-selectin expression [5].…”
Section: Prolactinmentioning
confidence: 99%
“…Inflammation is a process triggered by tissue injury secondary to infection, trauma, or ischemia and orchestrated by leukocytes and several molecules belonging to different families of mediators, such as cytokines, chemokines, and adhesion molecules in an attempt to restore tissue homeostasis [2]. Prolactin (PRL), the anterior pituitary hormone, is produced by many immune system cells [3] and acts as cytokine that influences proliferation, regulation, and communication of inflammatory cells [4]. Moreover, it is a co-factor of platelet activation [5] which is a crucial mechanism in arterial thrombogenesis.…”
Section: Introductionmentioning
confidence: 99%